Implementasi Akad Murabahah Pada Produk Pembiayaan Di Lembaga Keuangan Non-Bank (Studi Kasus BMT Cahaya Kebajikan) - Anisa, Fitri; Prawoto, Imam; Sunarya, Fitri R. (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Islamic non-bank financial institutions in Indonesia include Islamic insurance, Islamic cooperatives, Islamic capital markets and so on. Along with the times, the presence of non-bank financial institutions is starting to be favored by the public and in its implementation it must comply with sharia principles. The purpose of this study is to find out and understand how the Murabahah Contract is for Financing Products at BMT Cahaya Virtue and how the DSN-MUI Fatwa review regarding the implementation of the Murabahah Agreement for Financing Products at BMT Cahaya Virtue. This research method uses a combination method (mix method) with a concurrent triangulation design. The data was obtained by means of interviews, observations and in-depth questionnaires/questionsnaires to customers and members of BMT Cahaya Virtue, Bekasi City, in 2022, totaling 47 respondents and 10 informants. The results showed that the implementation of the Murabahah Contract on Financing Products at BMT Cahaya Virtue has been going well, but there are some discrepancies from the aspect of the customer's intention to purchase goods. Based on the research results, there are several customers who apply for murabahah financing not to buy goods but for other needs such as home renovations, paying for education fees and for non-purchasing purposes. In terms of the DSN-MUI Fatwa Review regarding the implementation of Murabahah Contracts on Financing Products at BMT Cahaya Virtue based on the results of data analysis, it can be seen that the Implementation of Murabahah Contracts on Financing Products at BMT Cahaya Virtue is very good.